Snf2 controls pulcherriminic acid biosynthesis and antifungal activity of the biocontrol yeast Metschnikowia pulcherrima. Issue 1 (20th May 2019) - Gore‐Lloyd, Deborah; Sumann, Inés; Brachmann, Alexander O.; Schneeberger, Kerstin; Ortiz‐Merino, Raúl A.; Moreno‐Beltrán, Mauro; Schläfli, Michael; Kirner, Pascal; Santos Kron, Amanda; Rueda‐Mejia, Maria Paula; Somerville, Vincent; Wolfe, Kenneth H.; et al.
Summary: Metschnikowia pulcherrima synthesises the pigment pulcherrimin, from cyclodileucine (cyclo(Leu‐Leu)) as a precursor, and exhibits strong antifungal activity against notorious plant pathogenic fungi. This yeast therefore has great potential for biocontrol applications against fungal diseases; particularly in the phyllosphere where this species is frequently found. To elucidate the molecular basis of the antifungal activity of M. pulcherrima, we compared a wild‐type strain with a spontaneously occurring, pigmentless, weakly antagonistic mutant derivative. Whole genome sequencing of the wild‐type and mutant strains identified a point mutation that creates a premature stop codon in the transcriptional regulator gene SNF2 in the mutant. Complementation of the mutant strain with the wild‐type SNF2 gene restored pigmentation and recovered the strong antifungal activity. Mass spectrometry (UPLC HR HESI‐MS) proved the presence of the pulcherrimin precursors cyclo(Leu‐Leu) and pulcherriminic acid and identified new precursor and degradation products of pulcherriminic acid and/or pulcherrimin. All of these compounds were identified in the wild‐type and complemented strain, but were undetectable in the pigmentless snf2 mutant strain. These results thus identify Snf2 as a regulator of antifungal activity and pulcherriminic acid biosynthesis in M. pulcherrima and provide a starting point for deciphering the molecular functions underlying the antagonistic activity of this yeast. Abstract : Metschnikowia pulcherrima is a strong antifungal yeast and a promising species for biocontrol applications. This multidisciplinary study on the M. pulcherrima mode of action compared a wild‐type isolate with a pigmentless mutant exhibiting reduced antifungal activity. The transcriptional regulator Snf2 was identified as an important regulator of antifungal activity of M. pulcherrima via PUL gene transcription, cyclodipeptide synthesis and additional, yet uncharacterised mechanisms.